Sensory processing in children with a history of maltreatment: an occupational therapy perspective. Issue 1 (2nd January 2020) - Howard, Amanda R. Hiles; Lynch, Amy K.; Call, Casey D.; Cross, David R.
ABSTRACT: Children with a history of maltreatment exhibit differences in a variety of domains, including sensory processing. However, little is known about how domain-specific sensory processing deficits differ by the type of maltreatment experienced. The focus of the current study was to investigate the relationship between abuse, neglect, or no maltreatment on seven sensory domains in a sample of adopted children. Caregivers of 408 adopted children ( M = 7.89, SD = 2.03) reported their child's history of maltreatment (abuse, neglect, or no maltreatment) and sensory processing abilities (Short Sensory Profile). Seventy-nine percent of the sample had sensory processing dysfunction (definite difference = 41%; probable difference = 38%). Children with a history of abuse (n = 147) had impairments in tactile sensitivity (84.4%) and taste/smell sensitivity (47.6%). Children with a history of neglect (n = 125) scored differently in underresponsive/seeks sensation (Neglect = 83.2%; Abuse = 57.8%). Both groups had significant differences in underresponsive/seeks sensation and auditory filtering. In summary, children with a history of adversity had domain-specific sensory processing differences that varied by the type of maltreatment experienced. These findings suggest that children may benefit from evaluation by an occupational therapist taking their specific history of maltreatment into account. Implications for allied health and mental health providers are discussed.